Parents' Perceptions of the Severity of Their Child's Autistic Behaviors and Differences in Parental Stress, Family Functioning, and Social Support. (June 2016) - Kissel, Susan D.; Nelson, W. Michael
The current study was designed to examine differences in parental stress, family functioning, and social supports among parents' perceptions of the severity of their child's autistic behaviors and a control group. To evaluate such differences, parental perceptions of children with autism and with typically developing children were compared. Parents of children with more severe autistic behaviors reported higher levels of parental stress and poorer ratings of their personal functioning in the family than parents of children with less severe autistic behaviors and typically developing children. The groups did not differ on the parents' report of the functioning of the family unit or on perceived helpfulness of family social support. More research is needed on this topic.